International Myeloma Working Group recommendations for the diagnosis and management of myeloma-related renal impairment - Dimopoulos, Meletios A.; Goldschmidt, Hartmut (Journal of clinical oncology, 2016)
PurposeThe aim of the International Myeloma Working Group was to develop practical recommendations for the diagnosis and management of multiple myeloma-related renal impairment (RI).MethodsRecommendations were based on published data through December 2015, and were developed using the system developed by the Grading of Recommendation, Assessment, Development, and Evaluation Working Group.RecommendationsAll patients with myeloma at diagnosis and at disease assessment should have serum creatinine, estimated glomerular filtration rate, and electrolytes measurements as well as free light chain, if available, and urine electrophoresis of a sample from a 24-hour urine collection (grade A). The Chronic Kidney Disease Epidemiology Collaboration, preferably, or the Modification of Diet in Renal Disease formula should be used for the evaluation of estimated glomerular filtration rate in patients with stabilized serum creatinine (grade A). International Myeloma Working Group criteria for renal reversibility should be used (grade B). For the management of RI in patients with multiple myeloma, high fluid intake is indicated along with antimyeloma therapy (grade B). The use of high-cutoff hemodialysis membranes in combination with antimyeloma therapy can be considered (grade B). Bortezomib-based regimens remain the cornerstone of the management of myeloma-related RI (grade A). High-dose dexamethasone should be administered at least for the first month of therapy (grade B). Thalidomide is effective in patients with myeloma with RI, and no dose modifications are needed (grade B). Lenalidomide is effective and safe, mainly in patients with mild to moderate RI (grade B); for patients with severe RI or on dialysis, lenalidomide should be given with close monitoring for hematologic toxicity (grade B) with dose reduction as needed. High-dose therapy with autologous stem cell transplantation (with melphalan 100 mg/m2 to 140 mg/m2) is feasible in patients with RI (grade C). Carfilzomib can be safely administered to patients with creatinine clearance > 15 mL/min, whereas ixazomib in combination with lenalidomide and dexamethasone can be safely administered to patients with creatinine clearance > 30 mL/min (grade A).
Gesehen am 25.10.2019